EVALUATING PLANT SPECIES USED IN VENDA (RSA) TO ADDRESS HIV/AIDS SIDE EFFECTS - Masevhe, N.; Eloff, J. N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
A total of 15 indigenous plants used by the local traditional medical practitioners for the treatment of candidiasis were collected. Hexane, acetone and methanol leaf extracts were evaluated for antifungal activity against Candida albicans using both microdilution1 and bioautography methods. Hexane leaf extracts of four indigenous plants were active against Candida albacans. Clerodendrum glabrum E. Mey had MIC value of 0.04 mg/ml, Faurea saligna, Schotia brachypetala and Strychnos potatorum all had MIC values of 0.08 mg/ml. Faurea saligna is the only plant that had substantial antioxidant activity. Bioautography revealed antifungal activity ranging from three to four components. The results support the use of these plants in folk medicine to treat candidiasis. Further work is in progress to conduct anti-inflammatory activity and bioassay-guided fractionation of the active extracts in order to isolate the active components and structure elucidation.References: 1. Eloff JN, 1988 Planta Medica 64, 711-714.